Antimicrobial Properties of Extracts from Cymbopogon Schoenanthus plant - Najmeddin Ellali; Fatma Habil; Siraj Embarek; Abdelkadous Youssef; Hodifa Salem; Salah Lafi (AlQalam Journal of Medical and Applied Sciences, 2025)
In this study, Experiments were performed to explore the antibacterial properties of an extract derived from Cympbogon Schonatus with water. This study evaluated the antibacterial activity of alcoholic and aqueous extracts of Cymbopogon Schoenanthus against four distinct bacterial species using the well diffusion method: two Gram-negative (S. aur, B. sub) and two Gram-positive (E. coli, S. typhi). The primary biologically active substances found in Cympbogon Schonatus include tannin, anthraquinone, terpene, coumarin, alkaloid, and saponin. While some bacteria showed resistance to the extract, Staphylococcus aureus and Bacillus subtilis were inhibited by the alcoholic extract of Cymbopogon Schoenanthus. These results suggest that extract from Cymbopogon Schoenanthus might be a viable choice in the hunt for natural antimicrobials. This study offers scientific insight that aids in assessing antibacterial values and investigating other pharmacological characteristics.